Lifestyle risk factors and control of chronic non-communicable diseases - Spasovski, Mome; Chingoska, Daniela; Pecev, Petar; Stamenova, Aleksandra (Institute of Public Health of Republic of Macedonia, 2018)
Non-communicable diseases, also known as modern-life diseases, are the leading cause of morbidity and mortality in the world and in the Republic of Macedonia. The complexity of their occurrence, often associated with multifactorial etiology and lifestyle risk factors, has a significant impact on preventive interventions, requiring broad intersectoral cooperation. The aim of the paper is to present thecurrent situation and burden of malignant neoplasms, cardiovascular diseases and diabetes in the Republic of Macedonia, associated with unhealthy lifestyle. Comparison between the mortality data for cardiovascular and malignant neoplasms and the prevalence of diabetes with data for Croatia, Slovenia and France was made. Data on morbidity and mortality for malignant neoplasms, cardiovascular diseases and diabetes was obtained from the reports on the health status of the population in the Republic of Macedonia, from the Register of chronic non-communicable diseases, as well as from the annual health reports for the population in R. Macedonia 2014 and 2015 and HFA database of the World Health Organization. The results are statistically analyzed, tabulated and graphically presented using an analytical-descriptive method. The data shows that in R. Macedonia the mortality rate from cardiovascular diseases is 545 per 100,000 inhabitants in 2014, and 180.4 per 100,000 inhabitants of malignant neoplasms. The prevalence of type 2 diabetes for 2013 expressed at the rate of 100.000 inhabitants is 2386.3. In R. Macedonia the data shows a continuous decline in hospital morbidity, both of cardiovascular diseases and malignant neoplasms, while ambulatory - polyclinic morbidity is on a steady increase. France shows the lowest rate of CVD mortality and malignant neoplasms. By analyzing the risk factors of chronic non-communicable diseases, we have noticed that a high percentage of the population in R. Macedonia has unhealthy lifestyle, especially the young population.
Keywords: chronic non-communicable diseases; risk factors; morbidity; mortality; evaluation; life-style